Antiplatelet Agents Have a Distinct Efficacy on Platelet Aggregation Induced by Infectious Bacteria - Hannachi, Nadji; Ogé-Ganaye, Emma; Baudoin, Jean-Pierre; Fontanini, Anthony; Bernot, Denis; Habib, Gilbert; Camoin-Jau, Laurence (Frontiers in Pharmacology, 2020)
Platelets are the cornerstone of hemostasis. However, their exaggerated aggregation induces deleterious consequences. In several diseases, such as infectious endocarditis and sepsis, the interaction between platelets and bacteria leads to platelet aggregation. Despite platelet involvement, no antiplatelet therapy is currently recommended in these infectious diseases. We aimed here, to evaluate, in vitro, the effect of antiplatelet drugs on platelet aggregation induced by two the bacterial pathogens most involved in infectious endocarditis, Staphylococcus aureus and Streptococcus sanguinis. Blood samples were collected from healthy donors (n=43). Treated platelet rich plasmas were incubated with three bacterial strains of each species tested. Platelet aggregation was evaluated by Light Transmission Aggregometry. CD62P expression was evaluated by flow cytometry. Aggregate organizations were analyzed by scanning electron microscopy. All the strains tested induced a strong platelet aggregation. Antiplatelet drugs showed distinct effects depending on the bacterial species involved with different magnitude between strains of the same species. Ticagrelor exhibited the highest inhibitory effect on platelet activation (p<0.001) and aggregation (p<0.01) induced by S. aureus. In the case of S. sanguinis, platelet activation and aggregation were better inhibited using the combination of both aspirin and ticagrelor (p<0.05 and p<0.001 respectively). Aggregate ultrastructures and effect of antiplatelet drugs observed by scanning electron microscopy depended on the species involved. Our results highlighted that the effect of antiplatelet drugs depended on the bacterial species involved. We might recommend therefore to consider the germ involved before introduction of an optimal antiplatelet therapy.